Civil Liability of Persons Related to Blood Transfusion with Allocation to the Blood Bank Department in the Conditions of Corona - Samaneh Zolfaghari; Abdolreza Farhadian (پژوهشهای حقوقی)
With the spread of the corona virus (Covid-19) in 2019, in addition to various physical, material and spiritual damages, it affected the social and economic life of many people, especially the people of Iran. Due to the fact that the mentioned virus appears in different ways in people, it may cause blood loss in infected patients and it is necessary to supply the need from the blood bank. Therefore, among the legal issues that can be raised in connection with the provision of blood by the blood bank in the conditions of the outbreak of the Covid-19 (Corona) virus, is the civil liability of the blood bank. According to this research, which was carried out using a descriptive-analytical method, blood bank employees are responsible for the patient's health during the transfusion of blood or its products under normal conditions, and they are responsible for compensation to the extent of the effective fault in the damage caused to the patient. Therefore, in emergency situations, such as the uncontrollable situation of Corona, the blood bank does not have any responsibility towards patients requesting blood, and if blood or blood products are requested and prepared for the patient according to the doctor's order, depending on the extent of the doctor's fault and lack of His supervision of the blood transfusion by the nurse, the civil liability is imposed on him, unless the fault of the nurse is proven for his improper performance. Finally, compensation for both material and moral damage, depending on the effectiveness of the performance of each of the above-mentioned departments, is charged to them individually or jointly.